Value Stream Mapping (VSM) Implementation as an Effort to Reduce Delays in the Procurement Process at PT DI - Deni Ahmad Taufik; Indra Maulana Fahturizal (Program Pascasarjana Magister Teknik Industri Universitas Mercu Buana, 2021)
PT DI is an oil and gas company, to support its production a good procurement process is needed. Procurement is an activity to get goods and services in a transparent, effective, and efficient. Based on data in 2017, there is 148 procurement with a value of less than 2.5 billion carried out by PT DI, from that data there are 43% of the procurement completed exceeding the predetermined initial target. Based on data in 2017, the procurement of A4100000121 has the highest delay rate of 32 days, therefore it is necessary to identify waste as an effort to reduce the time delay. The method used is Value Stream Mapping, this method is used to identify processes that contain waste so that existing waste can be removed. Based on the results of the study there was a decrease in time between Current State VSM and Future State VSM with a total time at Current State VSM of 39425 minutes and Future State VSM of 23085 minutes so that the time was decreased by 16340 minutes